Assessing mental health in children and adolescent with MTHFR polymorphisms: psychiatric disorders, executive functioning, and symptom profile in a Turkish clinical sample - ARMAN, AYŞE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
This study investigated behavioral phenotype, executive functions profile, and the existence of comorbid psychiatric disorders in children and adolescents with methylenetetrahydrofolate reductase (MTHFR) polymorphisms admitted to pediatric metabolism outpatient clinic. Internalizing problems, especially somatic complaints were common in patients with MTHFR. More than half of the cases had emotional control and initiating problems as executive function deficits. Attention-deficit/hyperactivity disorder was the most common psychiatric diagnosis, followed by anxiety disorder. Current findings emphasize that health care providers should be aware of the mental health needs of cases with MTHFR polymorphism in order to make plans of integrative physical and mental health care.
Keywords: Methylenetetrahydrofolate reductase (NADPH2); genetics; mental health; attention-deficit hyperactivity disorder; executive function